2019
DOI: 10.1021/acs.langmuir.8b04136
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Contact Angles on Lubricant-Impregnated Surfaces/SLIPS: From Superhydrophobicity to Electrowetting

Abstract: A fundamental limitation of liquids on many surfaces is their contact line pinning. This limitation can be overcome by infusing a nonvolatile and immiscible liquid or lubricant into the texture or roughness created in or applied onto the solid substrate so that the liquid of interest no longer directly contacts the underlying surface. Such slippery liquid-infused porous surfaces (SLIPS), also known as lubricant-impregnated surfaces, completely remove contact line pinning and contact angle hysteresis. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 45 publications
8
106
0
Order By: Relevance
“…On liquid-infused surfaces, the apparent contact angle of a droplet depends on the surface tensions and the intrinsic contact angles of all fluids involved in the system [24][25][26] . This rich interplay makes it much less trivial to predict the direction of droplet motion when there is a topographical gradient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On liquid-infused surfaces, the apparent contact angle of a droplet depends on the surface tensions and the intrinsic contact angles of all fluids involved in the system [24][25][26] . This rich interplay makes it much less trivial to predict the direction of droplet motion when there is a topographical gradient.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the direction of droplet motion, we can introduce the droplet-air effective interfacial tension 26 γ eff γ oa þ γ ow ; if S > 0ð lubricant encapsulation Þ; γ wa ; otherwise ; & and the following definitions of apparent contact angles cos θ eff wajs…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact angle of a droplet on a surface can be regulated by a voltage between the electrodes, which is called the electrowetting effect [110]. This electromechanical mechanism dominates the microfluidic behavior by modifying the interfacial tension [111]. More relevant to the bearing working conditions, it is observed that the nonpolar dielectric lubricant in the contact area of a steel ball and a metallic layer will spread along the surface under the action of an electric field [112].…”
Section: Interfacial Stress Induced By Electric Field: Electrowettingmentioning
confidence: 99%
“…When the lubricant encapsulates the droplet, the effective droplet-gas surface tension becomes g eff dg = g lg + g ld . 32 3…”
Section: 12mentioning
confidence: 99%